Variabilitas Harian Komunitas Ikan Pada Ekosistem Lamun Di Perairan Pulau Ketawai Kabupaten Bangka Tengah - Herlina Herlina; wahyu adi; eva utami (Akuatik: Jurnal Sumberdaya Perairan, 2018)
Fishes used seagrass ecosystem as nursery, spawning, feeding ground, daily ruaya and food for hebivorous fish. This research aims to describe the daily variability of fish communities in seagrass ecosystems, analyze seagrass communities and analyze seagrass associations with seagrass fish. The research was conducted in March 2017 in the waters of Ketawai Island, Central Bangka Regency. Line transect methode was used for seagrass data retrieval and swept area method for fish data capture.It was found that total number of individual fish as much as 244 ind/6.000m², consisting of 17 species during the day and 13 species at night. The highest abundance of daytime fish species Gerres filamentosus 68ind / 6.000m² and Hypoatherina barnesi 81ind/6.000m² at night. Diversity index is 1,917 at daytime and 1,074 at night. The uniformity indes is 0,677 at daytime and 0,419 at night. The dominance index is 0,258 at daytime and 0,583 at night. Spesies density, species frequency, species closure, Important Value Index of seagrass were dominated by three species of seagrass is Cymodocea rotundata, Thalassia hemprichii and Enhalus acoroides. Correspondence Analysis between the density of seagrass and the abundance of fish in the afternoon forming 2 groups and at night forming 3 groups of seagrass and fish associations. The Atherinidae fish family prefers the Thalassia hemprichii seagrass species.